The Balanced scorecard : translating strategy into action - Kaplan, Robert S.; Norton, David P. (Boston, Massachusetts : Harvard Business Review Press, 1996)
The book, while as comprehensive and complete as we could make it, is still a progress report. During the past three years, we have seen new developments and applications as the scorecard concept takes hold in more and more organization.
Part one : Measuring business strategy -- Part two : Managing business strategy
Includes index.
Keywords: STRATEGY